Cell Transfer Therapy for Cancer: Past, Present, and Future. (9th January 2014) - Qian, Xiaoling; Wang, Xian; Jin, Hongchuan
Abstract : Cell transfer therapy for cancer has made a rapid progress recently and the immunotherapy has been recognized as the fourth anticancer modality after operation, chemotherapy, and radiotherapy. Lymphocytes used for cell transfer therapy include dendritic cells, natural killer (NK) cells, and T lymphocytes such as tumor-infiltrating lymphocytes (TILs) and cytotoxic T lymphocytes (CTLs). In vitro activated or engineered immune cells can traffic to cancer tissues to elicit persistent antitumor immune response which is very important especially after immunosuppressive treatments such as chemotherapy. In this review, we overviewed recent advances in the exploration of dendritic cells, NK cells, and T cells for the treatment of human cancer cells.